A large and rapidly expanding odontogenic myxoma of the mandible - Sajad Ahmad Buch; Subhas G Babu; Kumuda Rao; Shruthi Rao; Renita Lorina Castelino (Wolters Kluwer Medknow Publications, 2017)
Odontogenic myxoma (OM) is a locally invasive benign tumour of the jaw originating from primordial mesenchymal tooth forming tissues. The average age for patients with OM is 25-30 years. OM has a predilection for posterior mandible. When it occurs in the maxilla, it is more invasive than that in the mandible. The recurrence rate of OM ranges between 10-33% with an average of 25%, hence, proper treatment design and close postoperative follow-up for the initial 2 years has been recommended. This is a case of a 30-year-old female showing a large expansile, rapidly growing lesion on the left side of the face involving left mandibular body and ramus. OM cases of this size and such rapid growth are very few in literature, and hence, makes this case one of the rare cases. Radiological investigations helped us to arrive at a diagnosis which was verified later by pre and postoperative histopathological examination. The patient was treated with left hemi-mandibulectomy and reconstruction was done using free fibula graft with titanium implant. The patient is presently under follow-up.